2016
DOI: 10.3844/ajabssp.2016.148.156
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Analysis of Supply Response of Rubber in Malaysia

Abstract: Supply response of rubber to changes in economic incentives is analysed using co-integration approach. Time series data is taken for the period 1990 to 2014 and the vector error correction model framework has been applied. The empirical results confirmed the existence of a unique long-run equilibrium relationship among planted acreage, the relative price of rubber and price of fertilizer. Further, the estimates suggested that rubber supply is significantly influenced by the relative price of rubber and the pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The authors also translated these estimates to the more commonly reported acreage elasticities of supply with respect to price values of 0.38 and 0.90 [ 14 ]. Other relevant studies have estimated values for this parameter, with respect to price, of 0.77 for rubber plantations in Malaysia [ 15 ], and of 0 to 1.55 for a range of crops in the US [ 16 ]. Based on this sample of estimates in the literature, our assumed AE value of 0.15 can be considered to be relatively conservative.…”
Section: Methodsmentioning
confidence: 99%
“…The authors also translated these estimates to the more commonly reported acreage elasticities of supply with respect to price values of 0.38 and 0.90 [ 14 ]. Other relevant studies have estimated values for this parameter, with respect to price, of 0.77 for rubber plantations in Malaysia [ 15 ], and of 0 to 1.55 for a range of crops in the US [ 16 ]. Based on this sample of estimates in the literature, our assumed AE value of 0.15 can be considered to be relatively conservative.…”
Section: Methodsmentioning
confidence: 99%
“…Cointegration methods offer a need for using the error correction model (ECM) for the same reason. Other studies that have used cointegration methods are Mustafa et al (2016) and Soontaranurak and Dawson (2015).…”
Section: Empirical Literature On Determinants Of Agricultural Exportmentioning
confidence: 99%
“…More recent studies have used co-integration and vector error correction approach since they provide more general dynamic structures and overcome the criticism of restrictive lag structure and spurious regression. Some of these studies include; Alias and Tang, (2005) to examine the supply of Palm oil in Malaysia; Mesike, et al, ( 2010) to examine rubber supply response in Nigeria; Darkwah and Verter, (2014) to examine cocoa bean supply in Ghana; Wani, et al, (2015) to analyze supply response of apples and pears in Jammu and Kashmir, India; Soontaranurak and Dawson, (2015) to analyze rubber acreage supply response in Thailand and Mustafa, et al, (2016) to examine the supply response of rubber in Malaysia. The general conclusion that has been drawn in all these studies is that cointegration and VECM approach as they exhibit more general dynamic structures than the Nerlovian models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The farmers' responsiveness can be estimated for either total production (output)/yield or the planted acreage. On one hand, the planted acreage is preferred in many studies of perennial crop supply response as it measures intended supply and it is more subjected to the control of the farmers unlike the output which is subjected to more random variations than acreage due to uncontrollable yield determine factors (Akiyama and Trivedi, 1987;Samarappuli and Bogahawatta, 1993;Soontaranurak and Dawson, 2015;Mustafa, et al, 2016). On the other hand, one can argue that the appropriate measure would be the volume of output produced since the level of output can easily change without changes in acreage (Mesike, et al, 2010;Ebi and Ape, 2014;Wani, et al, 2015).…”
Section: Empirical Approachmentioning
confidence: 99%
See 1 more Smart Citation